Antenatal Prediction of Neonatal Survival in Sacrococcygeal Teratoma. (5th February 2018) - Lee, Seung Mi; Suh, Dong Hoon; Kim, So Yeon; Kim, Min Kyoung; Oh, Sohee; Song, Sang Hoon; Kim, Hyun‐Young; Park, Chan‐Wook; Park, Joong Shin; Jun, Jong Kwan
Abstract : Objectives: In sacrococcygeal teratoma, the presence of high‐output cardiac failure resulting from arteriovenous shunting through the large tumor has been associated with an adverse outcome. The objective of this study was to determine whether the tumor size and cardiac biomarkers in cord blood can predict neonatal survival in sacrococcygeal teratoma. Methods: The study population consisted of 25 neonates with sacrococcygeal teratoma. Tumor size was calculated by the ellipsoid formula using dimensions measured by antenatal ultrasound ([length × width × depth in cm] × 0.52= volume in cm 3 ). To adjust the gestational age, the tumor volume index (tumor volume/biparietal diameter) was adopted in the analysis. Cardiac biomarkers for heart failure (N‐terminal pro‐B‐type natriuretic peptide [NT‐pro‐BNP] and cardiac troponin T [cTnT]) were measured in cord blood taken at the time of delivery. Results: The rate of neonatal death was 24% (6 of 25). The cases that resulted in neonatal death had a higher tumor volume index and higher concentrations of NT‐pro‐BNP and cTnT than those with survival. A tumor volume index of greater than 60 cm 3 /cm, elevated NT‐pro‐BNP (>2000 pg/mL), and elevated cTnT (>0.08 ng/mL) had sensitivity of 100% for prediction of neonatal death. Conclusions: The tumor volume index and cord blood biomarkers for heart failure can be promising prognostic markers for neonatal survival in sacrococcygeal teratoma.